India development and participation - Dráeze, Jean (Oxford University Press, 2010)
This book explores the role of public action in eliminating deprivation and expanding human freedoms in India. The analysis is based on a broad and integrated view of development, which focuses on well-being and freedom rather than the standard indicators of economic growth.